Radiosensitization of human breast cancer cells to ultraviolet light by 5-fluorouracil - SASAKI, KAZUHITO (D.A. Spandidos, 2011)
Ultraviolet light B (UVB) phototherapy is widely used to treat dermatological diseases and therefore may be a potential optional strategy in the treatment of a skin lesion infiltrated by a malignant tumor. Currently, little is known regarding the effect of UVB phototherapy on human breast cancer cells. The present study aimed to investigate the effect of UVB phototherapy, as well as the potential effect of 5-fluorouracil (5-FU), the first-line anticancer drug for breast cancer, on radiosensitizing MCF-7 human breast cancer cells, in an attempt to develop new therapeutic strategies for the treatment of locoregional recurrence of breast cancer. MCF-7 cells were incubated in the presence of 5-FU for 48 h, and UVB irradiation at 750 mJ/cm(2) was administered in the midterm of 5-FU treatment. The viability of MCF-7 cells was analyzed by the trypan blue staining method. Apoptosis was quantified by flow cytometry and Hoechst 33258 staining. The cell cycle was evaluated by flow cytometry after the staining of cells with propidium iodide. The combination treatment of 5-FU and UVB resulted in a strong potentiation of the inhibitory effect of MCF-7 cell growth, dependent on the intra-S phase cell cycle arrest and induction of apoptosis, when compared to treatment with 5-FU or UVB alone. In conclusion, 5-FU sensitized human breast cancer cells to UVB phototherapy, and this combination therapy is an effective and promising strategy for the treatment of breast cancer, particularly for locoregional recurrence.